Implementasi Pembelajaran Berdiferensiasi Aspek Proses terhadap Minat Belajar Peserta Didik Kelas 4 - Baskoro, Achmad Bagus; Nugroho, Aryo Andri; Prayito, Muhammad (TSAQOFAH, 2023)
Each student has various characteristics and learning needs, to fulfill this, differentiated learning can be done. This research aims to determine the implementation of differentiated learning on the learning interest of class IV students at SDN Panggung Lor. This research is experimental research with a pre-experimental design type. The research design is a one-group pretest-posttest design. The population and sample are class IV students. Data collection techniques use questionnaires and documentation. The data analysis technique uses the Wilcoxon Signed Rank Test. The Descriptive Statistics output results show that the average posttest value is 29.7037 which is greater than the pretest value, namely 24.6296. The output results of the Wilcoxon Signed Rank Test show that the overall Negative Ranks is 0. This means that there is no decrease in students' interest in learning after treatment. In Positive Ranks, it was found that 27 students experienced an increase in interest in learning after differentiated learning with an average increase of 14.00 and a total of 378.00 positive rankings. Ties has a value of 0, meaning there is no similar score between the pretest and posttest. From the results of the Test Statistics value of Asymp. Sig. (2-tailed) is smaller than 0.05 then Ha is accepted. This means that there are differences in students' learning interests before and after differentiated learning. So, based on the results of the research that has been carried out, it is concluded that differentiated learning increases the learning interest of class IV students at SDN Panggung Lor.